Genetic variation of lagocephalus lunaris species puffer fish using mitochondrial cytochrome b gene - Lim, Wand Suan (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study examines the genetic characteristic of Lagocephalus lunaris, an important indigenous puffer fish species in Sabah. The sequence analyses were carried out using 450 base pairs of the mitochondrial cytochrome b gene. A total of 60 samples were collected from two locations in the coastal areas of Sabah; Kudat (Pulau Mandi Darah) and Tawau. Phylogenetic analyses were done using two methods, Neighbor-joining (NJ) and Maximum Parsimony (PM). The result of phylogenetic analysis indicated the presence of two clusters of puffer fish; one consisted of samples only from Kudat, whereas another cluster consisted of samples from Tawau and a single sample from Kudat. A total of 9 haplotypes were found, with only one haplotype (H4) being shared between the two populations. The results also showed the presence of limited genetic variation among the two populations. Overall, this study indicated the potential of using cyt b mtDNA gene in detection of small genetic variation, or synonymous substitution between populations.